Gait Portrait Of Islamic Boarding School Qomaruddin In Indonesia - Abdul Muid (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2017)
To realize the ideals of boarding Qomaruddin Bungah Gresik, East Java, Indonesia is a multi-functional, then the boarding school Qomaruddin should not be shut out of the development of the boarding school although in the digital era, as now, as well as their identity as combatants proselytizing based Islamic education Aswaja, human resources development, management of the boarding school featuring an elegant and modern, as Bulding characteristics pesantren-based Islamic education in children's character to deliver the nation for the realization of full human development in this beloved State